Displaced within homelands : the IDPs of Bangladesh and the region - Abrar, Chowdhury Rafiqul; Lama, Mahendra P. (Refugee and Migratory Movements Research Unit, 2003)
On forced internal migration in Bangladesh, and South Asia; contributed articles.